A New PID Type Controller Based on Modified Crisp Logic - Abdeslam BENMAKHLOUF; Ghania Zidani; Djalal Djarah (ITEGAM-JETIA)
A PID type fuzzy logic controller (FLC) is a control scheme that utilizes fuzzy inference systems to replicate the behavior of a classical PID controller. This approach provides an alternative for systems where traditional PID control encounters difficulties, particularly in scenarios involving human expertise or non-linear behavior. In this study, we propose a novel PID-like controller that employs a modified crisp logic method—a rule-based approach designed to implement the reasoning process. This method aims to reduce processing time in fuzzy inference systems by using crisp sets instead of fuzzy sets and simple calculations to generate the output. Simulation results demonstrate the effectiveness of the proposed method, achieving comparable performance with the added benefit of reduced processing time.